-11(8m-6)=-2-7(12m-8)

Simple and best practice solution for -11(8m-6)=-2-7(12m-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11(8m-6)=-2-7(12m-8) equation:


Simplifying
-11(8m + -6) = -2 + -7(12m + -8)

Reorder the terms:
-11(-6 + 8m) = -2 + -7(12m + -8)
(-6 * -11 + 8m * -11) = -2 + -7(12m + -8)
(66 + -88m) = -2 + -7(12m + -8)

Reorder the terms:
66 + -88m = -2 + -7(-8 + 12m)
66 + -88m = -2 + (-8 * -7 + 12m * -7)
66 + -88m = -2 + (56 + -84m)

Combine like terms: -2 + 56 = 54
66 + -88m = 54 + -84m

Solving
66 + -88m = 54 + -84m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '84m' to each side of the equation.
66 + -88m + 84m = 54 + -84m + 84m

Combine like terms: -88m + 84m = -4m
66 + -4m = 54 + -84m + 84m

Combine like terms: -84m + 84m = 0
66 + -4m = 54 + 0
66 + -4m = 54

Add '-66' to each side of the equation.
66 + -66 + -4m = 54 + -66

Combine like terms: 66 + -66 = 0
0 + -4m = 54 + -66
-4m = 54 + -66

Combine like terms: 54 + -66 = -12
-4m = -12

Divide each side by '-4'.
m = 3

Simplifying
m = 3

See similar equations:

| -23+6x=5x+2(5x+2) | | 8p+21=-3(-8p-7) | | -11=8+r-3 | | (12x-8)+(12x-8)=(22x-11) | | 2(5+5k)=4+8k | | 1d/10-12 | | 3-1/t-2/t^2=0 | | lx-2l=2x+1 | | f(x)=7x^2+4x-3 | | 0.05x-0.1x+0.6=0.04x+2.22 | | (8x-3)+(8x-3)=(10x+30) | | =29*4 | | 7700+1900+700+160= | | 0.05x-0.1x+0.6=0.04+2.22 | | 0.05-0.1x+0.6=0.04+2.22 | | =(81+162t^2+81t^4) | | =sqrt(81+162t^2+81t^4) | | 4.25E-19= | | =32sin^2(t)cos^2(t) | | F=7/4(n-9) | | 1/2*3x*4x=216 | | (4x-5)(3x)= | | 325-x+650-2x+x=875 | | 4[6-(1+2x)]+10x=2(10x-3)+8x | | ln(3.59)=x | | -8x+12=15x-14 | | 8x+12y=50fory | | 5x+3a=5b | | 555+666x-3*x=534 | | 10t+2=2-7 | | 8-2x-5x-13=0 | | 2x+14=18y |

Equations solver categories